Communication Strategies and Personal Branding Education for Adolescent Life Planning and Early Marriage Prevention - Maulida Hidayah; Ade Nur Atikasari; Nasrudin Nasrudin (Jurnal IPTEK Bagi Masyarakat, 2026)
This community service program examined the use of educational, persuasive, and participatory communication strategies combined with personal-branding education to strengthen junior high school students’ understanding of life planning and early-marriage prevention. The activity was conducted at SMP Negeri 8 Banjarmasin with 30 students and included a pre-test, interactive presentations, educational videos, discussion, reflection, quizzes, and a post-test. A 10-item yes/no questionnaire assessed knowledge related to marriage-age planning and personal branding, and the results were analyzed descriptively using frequencies and percentages. Across the 10 indicators, affirmative responses increased from 30.0–50.0% at pre-test to 83.3–93.3% at post-test. The largest percentage-point gains concerned knowledge of the recommended marriage age for women under the BKKBN Pendewasaan Usia Perkawinan program (33.3% to 86.7%) and understanding of personal branding (30.0% to 83.3%). The findings show a descriptive increase in students’ immediate knowledge after the activity. Because the evaluation used a single-group pre-test/post-test design without a control group or inferential testing, the results should not be interpreted as causal evidence of program effectiveness.